THE MONSTER’S CHARACTERISTICS IN FRANKENSTEIN NOVEL BY MARY SHELLEY VIEWED FROM PERSONALITY TRAITS THEORY - Agustina, Agustina; Astuti, Anjar Dwi; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
This study aimed to analyze the character and characterization of monster in Frankenstein through theory of characterization by Boggs and Petrie. It was classified into characterization through appearance, action, dialogue, reactions of other characters, and choice of name of the character. The characteristics of monster were classified into the Big Five Theory by McCrae and Costa. They were openness, conscientiousness, agreeableness, extraversion, and neuroticism. The used of the theory aimed to reveal the personality of monster that had similarities with human personality. To know what the character and characterization of monster, the researcher applied descriptive-qualitative method. The result showed that monster had a terrible appearance. Through the dialogue, he was an ambitious creature. Through the action he was very interest in new things. The other characters felt frightened to see his horrible appearance. The monster was called ‘monster’ because of his terrible appearance. Based on the Big Five, monster was classified into conscientiousness because of his ambition. He was an agreeableness because of his kindness. He was classified into openness because he interested in new things. He was also categorized into neuroticism because he was very vengeful. The last type of the Big Five named extraversion was not found in this study because he was not a sociable creature. Thus, the monster who looked very terrible had many positiveness rather than the negative characteristics.